Uso del foro de discusión para desarrollar la escritura colaborativa en los estudiantes del quinto año de educación básica paralelo B de la escuela Alejandro Sergio Bermeo del cantón San José de Chimbo provincia Bolívar, año lectivo 2024-2025 - Cajo Uguña, Jessica Jamilex (2025)
The purpose of this project is to strengthen the development of collaborative writing skills in fifth-grade students of General Basic Education at Escuela Alejandro Sergio Bermeo, through the use of virtual forums. The need arises from observed deficiencies in idea organization, textual coherence, and spelling in written productions, which limit the development of linguistic, critical, and collaborative competencies. In response to this context, a strategy is proposed that leverages the advantages of the digital environment to promote interaction, creativity, and active participation in the writing process. The general objective of the study is to analyze the contribution of discussion forums to the development of collaborative writing in fifth-grade students of General Basic Education, parallel “B”, at Escuela Alejandro y Sergio Bermeo in the San José de Chimbo canton, during the 2024–2025 academic year. The research adopted a qualitative, explanatory approach, using techniques such as direct observation, a writing evaluation rubric, and a structured interview with the teacher. The sample consisted of 12 students and one teacher. The results showed a predominantly “good” performance in collaborative writing, with improvements in narrative coherence and idea integration. Additionally, the teacher expressed a favorable perception of collaborative work, despite having limited prior experience with virtual forums. It is concluded that the use of virtual forums strengthens written production, student participation, and digital competencies in rural contexts.